THE EFFECT OF TRAINABILITY ON THE PHYSICAL FITNESS OF YOUNG ATHLETES - Iveta Bonova; Stefan Kolimechkov; Petko Mavrudiev; Dimcho Mitsov; Daniela Dasheva (Scientific Publishing House. NSA Press, 2022)
Athletic talent represents a high level of trainability in a certain type of sport. The earlier the level of trainability is identified, the more effective the sports training of the athlete will be. The aim of this study was to establish the effect of trainability on the physical fitness of adolescent athletes as a consequence of an applied training program adequate to the age and sports experience of the athletes. This study included 52 young athletes (24 boys and 28 girls), divided into 4 groups: male athletes from the control group (n = 10, mean age 14.88 ± 1.29 years), male athletes from the experimental group (n = 14, mean age 13.72 ± 1.15 years), female athletes from the control group (n = 14, mean age 15.69 ± 1.00 years), and female athletes from the experimental group (n = 14, mean age 13.41 ± 1.68 years). The experimental groups followed a specialized 12-week program signed for the purposes of the study. All participants completed the Alpha-Fit physical fitness test battery in addition to specific fitness tests before and after the training intervention. This study showed significant differences with larger effect sizes in nearly all components of health-related and specific physical fitness for the experimental groups after the training intervention in contrast to the control groups. The results of the standing long jump in the male (184.57 ± 19.79 cm vs 200.79 ± 20.01 cm, effect size = 0.8) and female athletes (179.07 ± 18.56 cm vs 183.93 ± 16.26 cm, effect size = 0.3) from the experimental groups showed significantly better values after the intervention, which indicated that strength is highly trainable for both genders at this age (13-14 years of age). The results of this study showed that the effect of trainability on physical fitness was greater for the athletes who were following the specialized training program based on the expected transfer of development in physical qualities.